The Mediating Effect Of Learning Organisational Culture Between Leadership Styles And Readiness For Change: An Empirical Study In Yemen - Ali Al-Tahitah; Mohamed Mihlar Abdul Muthaliff; Nouna Sammar (Inderscience Enterprises Ltd., 2024)
Indexed by Scopus/ERA